2007
DOI: 10.21273/horttech.17.4.431
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Sources for Organic Vegetable Crops

Abstract: Fertilization is the most expensive cultural practice for the increasing numbers of organic vegetable growers in the United States. Nitrogen (N) is the most important and costly nutrient to manage, and cost-effective N management practices are needed for efficient organic vegetable production. There is a wide array of organic N sources available, but they vary in cost, N content, and N availability. Compost and cover crops are commonly used sources of N for vegetables because they are relatively inexpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
123
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(128 citation statements)
references
References 53 publications
3
123
0
2
Order By: Relevance
“…Furthermore, for irrigated organic vegetables grown under arid subtropical climate conditions, a very fast turnover of the amendments resulted in high C and N volatilization (Siegfried et al 2011). Consequently, sources, rate, timing, and method of amendment application will influence soil temperature, soil moisture, and nutrient availability (Gaskell and Smith 2007). Regrettably, few quantitative studies have been conducted on the nutrient release of surfaceapplied mulches, as found for fruit trees and perennial berries, in comparison with incorporated materials.…”
Section: B Nutrient Budgetingmentioning
confidence: 99%
“…Furthermore, for irrigated organic vegetables grown under arid subtropical climate conditions, a very fast turnover of the amendments resulted in high C and N volatilization (Siegfried et al 2011). Consequently, sources, rate, timing, and method of amendment application will influence soil temperature, soil moisture, and nutrient availability (Gaskell and Smith 2007). Regrettably, few quantitative studies have been conducted on the nutrient release of surfaceapplied mulches, as found for fruit trees and perennial berries, in comparison with incorporated materials.…”
Section: B Nutrient Budgetingmentioning
confidence: 99%
“…For high-level production of neutral protease we developed a strain, via UV mutagenesis, using Bacillus subtilis CICC 10265 as parent strain in this study. After being processed, the digestibility of the protein, which replete with FAAs and peptides of various molecular weights, is improved (Guo et al, 2007;Gaskell and Smith, 2007), and the product is easily absorbed (Rust, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen limitations are often an important factor limiting corn grain yield in organic systems (Berry et al 2002;Cavigelli et al 2008). Nitrogen management in organic cropping systems requires an integrated strategy of incorporating crop and cover crop residues and animal manures into soil to build and maintain soil organic matter and mineralizable soil N levels (Gaskell and Smith 2007;Berry et al 2002). Managing these systems sustainably requires that the buildup of mineralizable soil N be taken into consideration so that sufficient, but not excessive, rates of N inputs can be determined.…”
Section: Introductionmentioning
confidence: 99%